1991
DOI: 10.1037/0033-3204.28.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence and parallel processes: A case study of structural analysis of social behavior in supervision and short-term dynamic psychotherapy.

Abstract: The phenomenon of "parallel processes" in supervised short-term dynamic psychotherapy is examined using an intensive case study method. Structural Analysis of Social Behavior (SASB) was used to measure and track perceptions of interpersonal process by patient, therapist, and supervisor throughout a twenty-five session treatment. Implications of the findings for supervision and training, including developmental models, are discussed.Psychotherapy and supervision are major activities of psychologists yet compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 37 publications
2
36
0
1
Order By: Relevance
“…The earliest study was done by Doehrman (1976), who found that impasses in supervision between the supervisor and supervisee mirrored impasses in therapy between the therapist and the client. Alpher (1991) and Friedlander et al (1989) both provided evidence suggesting that parallel processes may exist and can be seen through an interdependence between the supervisory dyad and the therapy dyad. For example, Friedlander et al (1989) found that directiveness on the part of the supervisor was met by cooperativeness on the part of the supervisee.…”
Section: Clinical Supervisionmentioning
confidence: 94%
See 1 more Smart Citation
“…The earliest study was done by Doehrman (1976), who found that impasses in supervision between the supervisor and supervisee mirrored impasses in therapy between the therapist and the client. Alpher (1991) and Friedlander et al (1989) both provided evidence suggesting that parallel processes may exist and can be seen through an interdependence between the supervisory dyad and the therapy dyad. For example, Friedlander et al (1989) found that directiveness on the part of the supervisor was met by cooperativeness on the part of the supervisee.…”
Section: Clinical Supervisionmentioning
confidence: 94%
“…A few case studies have examined how parallel processes influence client outcome (Alpher, 1991;Doehrman, 1976;Friedlander, Siegel, & Brenock, 1989). The earliest study was done by Doehrman (1976), who found that impasses in supervision between the supervisor and supervisee mirrored impasses in therapy between the therapist and the client.…”
Section: Clinical Supervisionmentioning
confidence: 98%
“…For example, Alpher (1991) found similarities between the client's presentation to the counselor and the counselor's presentation to his supervisor in a 25-week study of parallel process. Similarly, Friedlander, Siegel, and Brenock (1989) identified instances in which the counselor's ease decreased in a counseling session, followed by a supervision session markedly more challenging to both the supervisor and counselor, indicating that the counselor was enacting in supervision dynamics from the counseling relationship.…”
mentioning
confidence: 84%
“…Although several researchers have empirically examined parallel process (e.g., Alpher, 1991;Doehrman, 1976;Friedlander, Siegel, & Brenock, 1989;Jacobsen, 2007), little has been written related to strategies for the effective use of parallel process in supervision. Although the definition of parallel process has evolved from Searles's (1955) conceptualization to suggest that it may originate from either the counselor-client relationship or the supervisor-counselor relationship, the focus of the present article is to examine an intervention used to navigate parallel process stemming from the counselor-client relationship.…”
mentioning
confidence: 99%
“…(p. 130) In considering such a pluralistically informed research agenda, what do we really know about psychoanalytic supervision empirically thus far? Some limited, yet useful supervision research has been done within the ranks of psychoanalysis or psychoanalytic psychotherapy (e.g., Zaslavsky, Nunes, & Eizirik, 2005), primarily giving attention to parallel process phenomena (Alpher, 1991;Caligor, 1981;Doehrman, 1976;Friedlander, Siegel, & Brenock, 1989;Jacobsen, 2007). But the vast majority of supervision investigations that are most relevant to our discussion here Á while drawing on psychoanalytically informed constructs Á have not been studies of psychoanalytic supervision at all, instead taking a more pan-theoretical perspective to the research variable under study.…”
Section: Pressing Needs Impressing Possibilities In Psychoanalytic Smentioning
confidence: 99%